1934
DOI: 10.1007/bf01888437
|View full text |Cite
|
Sign up to set email alerts
|

Über Wucherungen der Brunnerschen Drüsen

Abstract: Die nachfolgenden Ausffihrungen fiber Wucherungen der BrunnerschenDrtisen stfitzen sich einesteils auf die sorgf/~ltige, plunm~l~ige und fortlaufende Musterung yon ungef/~hr 2800 ZwOlffingerd/~rmen, andernteils auf gelegentlich gesammelte einschl~gige F/ille und haben vor allem die ]cnotige gutartige Form der in Rede stehenden Wueherung zum Gegenstande.Sie tritt auf dreierlei Weise in Erscheinung: 1. als ausgebreitete, 5rtlich zur Knotenbildung gesteigerte Hyperpla~'ie (Hyperplasia diffusa et nodosa glandularu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1955
1955
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…The diagnosis of Brunner's gland hyperplasia is supported by endoscopy and radiological findings. However, the sensitivity of endoscopy is 72-89% and occasionally, endoscopy is not useful in making the diagnosis.ss [5][6][7] Thus, we found that abdominal CT was useful in this case.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The diagnosis of Brunner's gland hyperplasia is supported by endoscopy and radiological findings. However, the sensitivity of endoscopy is 72-89% and occasionally, endoscopy is not useful in making the diagnosis.ss [5][6][7] Thus, we found that abdominal CT was useful in this case.…”
Section: Discussionmentioning
confidence: 65%
“…[5][6][7] This nodular hyperplasia (type 2) is often mistaken for a malignancy. The diagnosis of Brunner's gland hyperplasia is supported by endoscopy and radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…4 In 1934, Feyrter classified the abnormal glandular proliferation into the following three types: diffuse hyperplasia (type 1), nodular hyperplasia (type 2), and adenomatous hyperplasia (type 3). [5][6][7] This nodular hyperplasia (type 2) is often mistaken for a malignancy. The diagnosis of Brunner's gland hyperplasia is supported by endoscopy and radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pathomorphological features of Brunner's gland are characterized by the presence of nondysplastic, lobulated Brunner's glands. Brunner's gland hyperplasia was classified into three types: diffuse nodular hyperplasia, occupying most of the duodenum; local nodular hyperplasia, the most common type mainly present in the duodenal bulb; and adenomatous hyperplasia, with or without erosion or ulcer, which may be sessile or pedunculated [12,14,15]. Peetz et al [16] gave the definition of BGA and Brunner's gland hyperplasia by size that overgrowth of Brunner's glands forming a tumor larger than 1 cm in diameter was referred to as BGA, and less than 1 cm termed Brunner's gland hyperplasia.…”
Section: Etiology and Pathogenesis Of Bgamentioning
confidence: 99%